Calculation of Optimum Volume of Material Delivery - I. M. Babuk; S. D Sushch (Наука и техника)
The paper proposes a model which makes it possible to calculate optimum volume of material delivery to an enterprise. It provides minimum expenses which are intended for meeting annual material requirements.The proposed model takes into account imputed expenditures which are non-eamed revenue of the enterprise due to freezing of circulating medium at storage reserve.Calculative example of optimum volume of material delivery is given in the paper.